2013
DOI: 10.1071/wr13015
|View full text |Cite
|
Sign up to set email alerts
|

Is the reptile community affected by Eucalyptus wandoo tree condition?

Abstract: Context. Large portions of the world's forests and woodlands are currently affected by declines in canopy condition of dominant tree species; however, the effects of these declines on faunal communities are largely unknown. Eucalyptus wandoo woodlands in the Southwest region of Western Australia have demonstrated declines in condition since the early 1990s. Such declines in tree condition can result in reduced understorey vegetation, increased leaf-litter cover and coarse woody debris, potentially altering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The SWWA has experienced a continuous decline in rainfall and increases in temperature since the mid-1970s (Bates et al, 2008). The decreasing health of several tree species and changes within associated fauna and soil communities have been linked with these changing climatic conditions (Cai et al, 2010;Brouwers et al, 2012;Moore et al, 2013) and might represent early indications of a decrease in the resilience of the forest ecosystem (Reyer et al, 2015). The climatic changes in SWWA are projected to continue (CSIRO and BOM, 2007) as well as for Mediterranean climate regions around the world (Klausmeyer and Shaw, 2009;IPCC, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The SWWA has experienced a continuous decline in rainfall and increases in temperature since the mid-1970s (Bates et al, 2008). The decreasing health of several tree species and changes within associated fauna and soil communities have been linked with these changing climatic conditions (Cai et al, 2010;Brouwers et al, 2012;Moore et al, 2013) and might represent early indications of a decrease in the resilience of the forest ecosystem (Reyer et al, 2015). The climatic changes in SWWA are projected to continue (CSIRO and BOM, 2007) as well as for Mediterranean climate regions around the world (Klausmeyer and Shaw, 2009;IPCC, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Relationships indicated that not only E. wandoo condition, but also understorey habitat, were strongly correlated with the small mammal community, highlighting that management should include preservation of E. wandoo trees and the understorey microhabitat necessary for shelter and food resources by small mammals, as seen in other studies (Stephens et al 2012). It should be noted that generalising results over the two locations can be difficult; however, the heterogeneous nature of the E. wandoo decline (and the microhabitat) (Brouwers et al 2013;Moore et al 2013) meant there was habitat variability within a site, as well as a location. Indices of tree canopy condition were retained in the best models describing both mammal abundance and species richness.…”
Section: Discussionmentioning
confidence: 90%
“…Ten years ago it was noted that trees within two of the three largest patches, the Wandoo Conservation Park and the Dryandra State Forest, were showing signs of decline with symptomatic retraction or loss of canopy (Wandoo Recovery Group 2006;Brouwers et al 2013). Declines of this eucalypt occur heterogeneously, where healthy trees can be adjacent to declining trees (Brouwers et al 2013;Moore et al 2013), differing from other eucalypt decline where large-scale canopy loss occurs (e.g. Eucalyptus marginata, jarrah) (Matusick et al 2012).…”
Section: Introductionmentioning
confidence: 99%